Flexible Ureteroscopic Holmium Laser Infundibulotomy and Lithotrypsy for the Management of Calyceal Diverticular Stone with Infundibular Atresia: A Case Report - Sah, Anil Kumar; Maharjan, Bipin; Adhikari, Mahesh Bahadur (Birat Journal of Health Sciences, 2021)
Renal calyceal diverticulum is a non-secretary urothelium cavity in the renal parenchyma communicating with calyx allowing for passive filling with urine. Calyceal diverticula are found incidentally in 0.21% to 0.6% of intravenous urograms in adults. Stone formation occurs in about 10-50% cases of renal calyceal diverticula. Symptomatic case needs treatment. Digital flexible ureteroscopy with Holmium laser infundibulotomy and laser lithotripsy is beneficial in terms of shorter hospital stay, better stone clearance and minimal complications in comparison with those of other modalities. Cases of stenotic infundibulum have been addressed adequately but infundibular atresia has been rarely reported. Therefore, we present a symptomatic case of calyceal diverticular stone with infundibular atresia managed by disposable flexible ureteroscopy with holimium laser infundibulotomy and laser lithotripsy.